2020
DOI: 10.1101/2020.06.09.20125237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 related mortality and spread of disease in long-term care: a living systematic review of emerging evidence

Abstract: Background: Policy responses to mitigate the impact of the COVID-19 pandemic on long-term care (LTC) require robust and timely evidence on mortality and spread of the disease in these settings. The aim of this living systematic review is to synthesise early international evidence on mortality rates and incidence of COVID-19 among people who use and provide LTC. Methods: We report findings of a living systematic review (CRD42020183557), including studies identified through database searches up to 5 June 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 65 publications
4
60
0
3
Order By: Relevance
“…In Scottish care homes, a larger proportion of COVID-19 deaths are reported to have occurred than in English care homes (47% vs 28%), 13 , 20 although these proportions are both within the range reported internationally (from 24% in Hungary to 82% in Canada). 1 This difference could reflect differing hospital admission practices in England and Scotland since approximately 12% of COVID-19-related deaths of care home residents in England are in hospital 21 versus only 4% in our study. A London point-prevalence study of four care homes with about 400 residents found 26% mortality, higher than that noted in our study, which probably reflects selection of care homes with large outbreaks.…”
Section: Discussionmentioning
confidence: 69%
“…In Scottish care homes, a larger proportion of COVID-19 deaths are reported to have occurred than in English care homes (47% vs 28%), 13 , 20 although these proportions are both within the range reported internationally (from 24% in Hungary to 82% in Canada). 1 This difference could reflect differing hospital admission practices in England and Scotland since approximately 12% of COVID-19-related deaths of care home residents in England are in hospital 21 versus only 4% in our study. A London point-prevalence study of four care homes with about 400 residents found 26% mortality, higher than that noted in our study, which probably reflects selection of care homes with large outbreaks.…”
Section: Discussionmentioning
confidence: 69%
“…Expert commentary on existing data has identified care and non-care staff, visitors and resident discharges from hospital as possible vectors for the introduction of COVID-19 into care homes, particularly where testing is not available, 14 and the discharge back to their care home of untested SARS-CoV-2 positive individuals has been suggested as a risk factor for outbreaks in these settings 15,16 . Studies reporting evidence from testing all staff and residents in specific care homes has suggested high proportions of asymptomatic cases, particularly amongst older residents, than were initially assumed 7,14,17 . This suggests the risk of importing COVID-19 into care homes via hospital discharge of untested asymptomatic residents has been underestimated.…”
Section: What Is Already Known On This Subjectmentioning
confidence: 99%
“…In response to the spread of SARS-CoV-2, governments, public health agencies and care organisations across the world have taken drastic measures to curb the ensuing COVID-19 pandemic. On top of community interventions for the general public, long-term care facilities for people with disabilities and elderly people limited visits, activities and supportive services (Salcher-Konrad et al 2020). These measures were taken to limit the risk of people acquiring infection in aggregate care settings from other clients, visitors or care staff (nosocomial transmission) and followed on early reports of actual outbreaks in nursing homes (e.g.…”
mentioning
confidence: 99%